Oral Microbiome and Dental Caries Development - Josie Shizhen Zhang; Chun-Hung Chu; Ollie Yiru Yu (MDPI AG, 2022)
Dental caries remains the most prevalent oral disease worldwide. The development of dental caries is highly associated with the microbiota in the oral cavity. Microbiological research of dental caries has been conducted for over a century, with conventional culture-based methods and targeted molecular methods being used in order to identify the microorganisms related to dental caries. These methods' major limitation is that they can identify only part of the culturable microorganisms in the oral cavity. Introducing sequencing-based technology and bioinformatics analysis has boosted oral microbiome research and greatly expanded the understanding of complex oral microbiology. With the continuing revolution of molecular technologies and the accumulated sequence data of the oral microbiome, researchers have realized that microbial composition alone may be insufficient to uncover the relationship between caries and the microbiome. Most updated evidence has coupled metagenomics with transcriptomics and metabolomics techniques in order to comprehensively understand the microbial contribution to dental caries. Therefore, the objective of this article is to give an overview of the research of the oral microbiome and the development of dental caries. This article reviews the classical concepts of the microbiological aspect of dental caries and updates the knowledge of caries microbiology with the results of current studies on the oral microbiome. This paper also provides an update on the caries etiological theory, the microorganisms related to caries development, and the shifts in the microbiome in dental caries development.